2019
DOI: 10.1161/strokeaha.119.024638
|View full text |Cite|
|
Sign up to set email alerts
|

Obesity Paradox in Intracerebral Hemorrhage

Abstract: Background and Purpose— Although obesity is an established risk factor for cardiovascular disease and stroke, studies have shown evidence of an obesity paradox—a protective effect of obesity in patients who already have these disease states. Data on the obesity paradox in intracerebral hemorrhage is limited. Methods— Clinical data for adult intracerebral hemorrhage patients were extracted from the National Inpatient Sample between 2007 and 2014. Multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Kim et al 12 and Sun et al 24 showed that obesity was associated with a lower risk of long-term death. Hoffman et al 23 and Persaud et al 25 also found that obesity is associated with decreased in-hospital mortality. But other studies [12][13][14] found no evidence of obesity paradox in 30-day mortality after ICH.…”
Section: Discussionmentioning
confidence: 96%
“…Kim et al 12 and Sun et al 24 showed that obesity was associated with a lower risk of long-term death. Hoffman et al 23 and Persaud et al 25 also found that obesity is associated with decreased in-hospital mortality. But other studies [12][13][14] found no evidence of obesity paradox in 30-day mortality after ICH.…”
Section: Discussionmentioning
confidence: 96%
“…9,58 Table 1 presents additional studies regarding the beneficial or favorable relationship of the obesity paradox with stroke. [59][60][61][62][63][64][65] However, some studies indicate that for obesity class III (40 to 49.9 kg/m 2 ) the paradox is no longer applicable due to the U or J shaped effect. 30 Further, there is a clear association between BMI-related mortality and this effect.…”
Section: Current Evidence For the Obesity Paradox And Stroke Relationmentioning
confidence: 99%
“…Very few studies regarding obese patients and the paradox relation with stroke reach an adequate level of evidence. For example, Persaud et al 65 in 2019 showed that obese patients with intracranial hemorrhage had a better survival rate during the in-hospital stay, and they credited this result to statins intake and its pleiotropic effect with respective anti-inflammatory and anti-thrombotic properties that might reduce the infarcted area and increase survival rates. Regarding the relation of BMI to outcomes after a surgical procedure, the results might be a little controversial, and this may be because of the difference in the treatment and its frequency.…”
mentioning
confidence: 99%
“…Traditionally, obesity has been regarded as a well-established risk factor for cardiovascular diseases and stroke. Nevertheless, a growing body of evidence has suggested that an "obesity paradox"-namely that there is an inverse association between obesity and clinical outcomes-exists for patients with hypertension (Kleinloog et al, 2018) coronary artery diseases (Uretsky et al, 2007;Wang et al, 2015), atrial fibrillation (Sandhu et al, 2016), intracerebral hemorrhage (Persaud et al, 2019), and ischemic stroke (Rodríguez-Castro et al, 2019;Liu et al, 2021). Likewise, this paradoxical phenomenon was also observed in patients with SAH (Rinaldo et al, 2019;Rautalin et al, 2020), suggesting a potential protective effect of increased BMI on the risk of adverse events after presenting intracranial aneurysms.…”
Section: Introductionmentioning
confidence: 99%